Oleic Acid Protects Caenorhabditis Mothers From Mating-Induced Death and the Cost of Reproduction - Choi, Leo S.; Shi, Cheng; Ashraf, Jasmine; Sohrabi, Salman; Murphy, Coleen T. (Frontiers in Cell and Developmental Biology, 2021)
Reproduction comes at a cost, including accelerated death. Previous studies of the interconnections between reproduction, lifespan, and fat metabolism in C. elegans were predominantly performed in low-reproduction conditions. To understand how increased reproduction affects lifespan and fat metabolism, we examined mated worms; we find that a Δ9 desaturase, FAT-7, is significantly up-regulated. Dietary supplementation of oleic acid (OA), the immediate downstream product of FAT-7 activity, restores fat storage and completely rescues mating-induced death, while other fatty acids cannot. OA-mediated lifespan restoration is also observed in C. elegans mutants suffering increased death from short-term mating, and in mated C. remanei females, indicating a conserved role of oleic acid in post-mating lifespan regulation. Our results suggest that increased reproduction can be uncoupled from the costs of reproduction from somatic longevity regulation if provided with the limiting lipid, oleic acid.